PSYCHOLOGICAL-PEDAGOGICAL ANALYSIS OF THE NEGATIVE EFFECTS OF INFORMATION THREATS ON PERSONALITY DEVELOPMENT - Nishanov Abduvokhid Tursunaliyevich (Western European Studies, 2024)
This article delves into the psychological and pedagogical analysis of the negative effects posed by information threats on the development of personality. It examines how computers and information systems, as integral parts of human activities, influence mental processes and transform both individual actions and human activity as a whole. The study draws heavily on the cultural-historical theory of mental development, emphasizing the transformation and complication of mental functions through interaction with information technology. A substantial focus is placed on the Internet's role in these dynamics, including its implications for cognitive, communicative, and personal aspects of human activities, and its contribution to the development of virtual identities and online communication dynamics. The article also explores the ethical aspects and behavioral norms evolving within virtual communities.
Keywords: information threats; personality development; cultural-historical theory